Kemampuan Literasi Matematika Siswa dengan Gaya Belajar Kinestetik - Fitria Sulistyowati; Istiqomah Istiqomah; Betty Kusumaningrum; Krida Singgih Kuncoro; Tiara Pramudianti; Arif Usman (Universitas Nusa Cendana, 2021)
This research is a descriptive study with a qualitative approach that aims to describe the mathematical literacy ability of students with kinesthetic learning styles. The subject in this study was a fifth-grade elementary school (SD) student with a kinesthetic learning style. Data were collected using documentation, interviews, and observation. Data analysis techniques used in this research are data reduction, data presentation, verification, and decision. This study gives the results that: (1) the level of mathematical literacy ability of the research subjects is at the Cakap level and needs to be given proper learning, namely problem-based learning; (2) some calculation notations are not proper so that it is necessary to strengthen problem-solving procedures so that there are no errors in strategy selection. The results of this study are expected to be used as a reference for further research related to students' mathematical literacy skills with kinesthetic learning styles.